2021
DOI: 10.1021/acsaem.1c02463
|View full text |Cite
|
Sign up to set email alerts
|

Facile Self-Template Synthesis of a Nitrogen-Rich Nanoporous Carbon Wire and Its Application for Energy Storage Devices

Abstract: Heteroatom doping, pore engineering, and morphology design are efficient strategies to develop a high-performance electrode material for supercapacitors. In the periodic table of the elements, nitrogen is adjacent to carbon and their atomic radii are close to each other; therefore, the doping of nitrogen atoms can cause the lattice of the carbon material to be substantially distorted. In this study, a facile one-step self-template strategy for synthesizing a highly nitrogen-doped nanoporous carbon wire (denote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In Figure S3 , the Ragone plots of C−1 show that the specific energy was calculated to be much better than the others at the same specific power. It had a good specific energy of 109 W·h·kg −1 at a specific power of 980 W·kg −1 , which was higher than the values of other carbon-based materials [ 20 , 36 , 37 ]. Furthermore, the specific energy of C−1 remained as high as 73.5 W·h·kg −1 even at a specific power of 9800 W·kg −1 .…”
Section: Resultsmentioning
confidence: 87%
“…In Figure S3 , the Ragone plots of C−1 show that the specific energy was calculated to be much better than the others at the same specific power. It had a good specific energy of 109 W·h·kg −1 at a specific power of 980 W·kg −1 , which was higher than the values of other carbon-based materials [ 20 , 36 , 37 ]. Furthermore, the specific energy of C−1 remained as high as 73.5 W·h·kg −1 even at a specific power of 9800 W·kg −1 .…”
Section: Resultsmentioning
confidence: 87%
“…For the samples of N,S-PC 1:4, 1:8, and 1:12, a new peak located at 400.5 eV (corresponding to N 1s) was observed, and two other peaks appearing at 164.5 and 228.2 eV were attributed to S 2p and S 2s, respectively, which proved that the N and S heteroatoms were successfully doped into the carbon framework . The high-resolution XPS C 1 s spectrum of the N,S-PC (1:12) (Figure S5) main peak, centered at approximately 284.60 eV, is attributed to C–C and/or CC, which can be fitted into four parts: CC (283.28 eV), C–C/C–O (284.68 eV), C–N (287.78 eV), and O–CO (290.53 eV) . The N 1 s spectrum (Figure e) is assigned to pyridinic N (N-6, 398.3 eV), pyrrolic N (N-5, 400.1 eV), and quaternary N (N-Q, 401.2 eV).…”
Section: Resultsmentioning
confidence: 84%
“…27 The high-resolution XPS C 1 s spectrum of the N,S-PC (1:12) (Figure S5) main peak, centered at approximately 284.60 eV, is attributed to C−C and/or C� C, which can be fitted into four parts: C�C (283.28 eV), C− C/C−O (284.68 eV), C−N (287.78 eV), and O−C�O (290.53 eV). 38 The N 1 s spectrum (Figure 2e) is assigned to pyridinic N (N-6, 398.3 eV), pyrrolic N (N-5, 400.1 eV), and quaternary N (N-Q, 401.2 eV). N-6 and N-5 can produce more defects, provide more active sites, and induce pseudocapacitance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The oxygen content in the samples decreased with increasing power owing to the gradual decrease in oxygen content with sufficient temperature at higher powers (10.51%, 8.06%, and 7.95% were the oxygen content of PC-325W-0.4, PC-425W-0.4, and PC-475W-0.4, respectively). However, the content of oxygen element in PC-275W-0.4 was 9.85%, which may be caused by an incomplete reaction where the low temperature of the reaction system inhibited the carbonization of the potassium citrate at lower power …”
Section: Resultsmentioning
confidence: 99%
“…42 To study the surface properties and pore structure, N 2 adsorption−desorption isotherms of PCs were measured at 77 K. Figure 3c shows the adsorption and desorption isotherms of PC-375W-1.0, PC-375W-0.75, PC-375W-0.5, PC-375W-0.4, and PC-375W-0.25, which conform to type I adsorption desorption isotherms. 43 It was clearly observed that the isotherms in the low pressure region and the high pressure region rise rapidly, which proved the existence of micropores and macropores. 44 The specific surface area, microporous surface area, pore volume, microporous volume, and average pore diameter of the PC samples are all listed in Table S3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%